PENGARUH DUKUNGAN SOSIAL DAN STRATEGI NAFKAH TERHADAP KESEJAHTERAAN SUBJEKTIF KELUARGA USIA PENSIUN - Sulastri, Sri; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2014)
The retirement age is often refers with periods of decline of welfare including economic condition, physical, psychological, and social. A supported environment and availability of alternative source of income will determine the happines of retirement age. This aim of this study was to analyze the influence of social support and livelihood strategies on subjective well-being of family at retirement age. This study used cross sectional study design. This research involved 154 families with husband or wives aged 56 years old or above and being retired. The samples were selected purposively and grouped into two categories (government officer and nongovernment officer). Data were collected by interview used questionnaire and analyzed by compare means independent sample t-test and multiple linear regression. Results of this study indicated that subjective well-being of government officer families was higher than nongovernment officer. Factors that influenced subjective well-being of family at retirement age were family income, social support, and livelihood strategies.